Simulation of the hydrogen ground state in stochastic electrodynamics. (7th October 2015) - Nieuwenhuizen, Theo M; Liska, Matthew T P
Abstract: Stochastic electrodynamics is a classical theory which assumes that the physical vacuum consists of classical stochastic fields with average energy in each mode, i.e., the zero-point Planck spectrum. While this classical theory explains many quantum phenomena related to harmonic oscillator problems, hard results on nonlinear systems are still lacking. In this work the hydrogen ground state is studied by numerically solving the Abraham–Lorentz equation in the dipole approximation. First the stochastic Gaussian field is represented by a sum over Gaussian frequency components, next the dynamics is solved numerically using OpenCL. The approach improves on work by Cole and Zou 2003 by treating the full problem and reaching longer simulation times. The results are compared with a conjecture for the ground state phase space density. Though short time results suggest a trend towards confirmation, in all attempted modellings the atom ionises at longer times.